Examining Lavender Marriage: Social Influence and Identity Construction in a Heteronormative Context - Jacklin Stefany Manafe; Jeni M. Ataupah; Hildigardis M.I. Nahak (Jurnal Pluralis, 2024)
Lavender marriage, a term referring to a heterosexual marriage arranged as a cover to hide the non-heterosexual sexual orientation of one or both partners, has become an interesting phenomenon to analyze in a heteronormative social context. This article examines how social pressure and heteronormative norms influence an individual's decision to engage in a lavender marriage and how this impacts the construction of sexual and gender identities. This analysis reveals that lavender marriages not only reflect an attempt to maintain sexual privacy in a repressive social environment but also serve as a tool to maintain social status in a society that marginalizes non-heterosexual identities.